2017
DOI: 10.1002/app.45454
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐induced grafting of poly(ethylene glycol) onto polyamide thin film composite membranes

Abstract: In this study, the surface grafting of poly(ethylene glycol) (PEG) onto commercial polyamide thin film composite (TFC‐PA) membranes was carried out, using ultraviolet photo‐induced graft polymerization method. The attenuated total reflection Fourier transform infrared spectra verify a successful grafting of PEG onto the TFC‐PA membrane surface. The scanning electron microscope and atomic force microscope analyses demonstrate the changes of the membrane surface morphology due to the formation of the PEG‐grafted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Additionally, a previous study reported that the thin film composite-PA-g-polyethylene glycol (PEG) spectra, compared to the unmodified version, displayed wide bands approximately at 3400 and 2850 cm −2 , indicative of the presence of -OH groups and the -CH 2 group from the PEG-grafted layer. The results derived from FTIR analyses strongly affirm the successful grafting of PEG onto the surface of the thin film composite-g-PA material (Hong Anh Ngo et al, 2017).…”
Section: Characterization Of Functional Groupssupporting
confidence: 54%
See 1 more Smart Citation
“…Additionally, a previous study reported that the thin film composite-PA-g-polyethylene glycol (PEG) spectra, compared to the unmodified version, displayed wide bands approximately at 3400 and 2850 cm −2 , indicative of the presence of -OH groups and the -CH 2 group from the PEG-grafted layer. The results derived from FTIR analyses strongly affirm the successful grafting of PEG onto the surface of the thin film composite-g-PA material (Hong Anh Ngo et al, 2017).…”
Section: Characterization Of Functional Groupssupporting
confidence: 54%
“…Studies on the grafting of poly(ethylene glycol) onto PA membrane composites have shown, through AFM analysis, that the surface morphology of the membrane changed due to the formation of the top poly(ethylene glycol) grafting layer. The grafting yield increased with longer grafting time and/or higher poly(ethylene glycol) concentration (Hong Anh Ngo et al., 2017). However, AFM has some limitations, including its slow imaging speed, the risk of contamination of the contact mode probe, and the high operational skill requirements.…”
Section: Characterization Of Grafted Polymersmentioning
confidence: 99%
“…Photo-induced graft polymerization and plasma polymerization have also been used to incorporate different PEG-based moieties on the active layer of TFC membranes to develop membranes with higher fouling resistance and separation properties 15 , 16 . Nevertheless, the direct grafting of PEG-based polymers onto the membrane surface would find limited industrial applications due to the need for multi-step reactions under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, numerous research studies have been devoted to explore the underlying correlations between the synthesis parameters for the PA and desalination properties of the final TFCs. The most important parameters include the type and concentration of monomers and additives, organic solvents, reaction time, curing time and temperature, posttreatment strategies, and fabrication method of the PA layer …”
Section: Introductionmentioning
confidence: 99%